Assessment of In Vitro COPD Models for Tobacco Regulatory Science: Workshop Proceedings, Conclusions and Paths Forward for In Vitro Model Use. Issue 2 (May 2016) - Behrsing, Holger; Raabe, Hans; Manuppello, Joseph; Bombick, Betsy; Curren, Rodger; Sullivan, Kristie; Sethi, Sanjay; Phipps, Richard; Tesfaigzi, Yohannes; Yan, Sherwin; D'Ruiz, Carl; Tarran, Robert; et al.
The Family Smoking Prevention and Tobacco Control Act of 2009 established the Food and Drug Administration Center for Tobacco Products (FDA-CTP), and gave it regulatory authority over the marketing, manufacture and distribution of tobacco products, including those termed 'modified risk'. On 8–10 December 2014, IIVS organised a workshop conference, entitled Assessment of In Vitro COPD Models for Tobacco Regulatory Science, to bring together stakeholders representing regulatory agencies, academia, industry and animal protection, to address the research priorities articulated by the FDA-CTP. Specific topics were covered to assess the status of current in vitro technologies as they are applied to understanding the adverse pulmonary events resulting from tobacco product exposure, and in particular, the progression of chronic obstructive pulmonary disease (COPD). The four topics covered were: a) Inflammation and Oxidative Stress; b) Ciliary Dysfunction and Ion Transport; c) Goblet Cell Hyperplasia and Mucus Production; and d) Parenchymal/Bronchial Tissue Destruction and Remodelling. The 2.5 day workshop included 18 expert speakers, plus poster sessions, networking and breakout sessions, which identified key findings and provided recommendations to advance the in vitro technologies and assays used to evaluate tobacco-induced disease etiologies. The workshop summary was reported at the 2015 Society of Toxicology Annual Meeting, and the recommendations led to an IIVS-organised technical workshop in June 2015, entitled Goblet Cell Hyperplasia, Mucus Production, and Ciliary Beating Assays, to assess these assays and to conduct a proof-of-principle multi-laboratory exercise to determine their suitability for standardisation. Here, we report on the proceedings, recommendations and outcomes of the December 2014 workshop, including paths forward to continue the development of non-animal methods to evaluate tissue responses that model the disease processes that may lead to COPD, a major cause of mortality worldwide.